Contribution of Social Capital in Strengthening Community-Based Education (CBE) in Madrasah - Choiri, Moh. Miftachul; Sidiq, Umar (Cendekia: Kependidikan dan Kemasyarakatan, 2023)
This paper aims to describe and analyze the madrasahs’ activities in encouraging community-based education (CBE) reinforcement. The setting of this research was Madrasah Aliyah (MA) Nurul Mujtahidin Mlarak Ponorogo. This research employed a qualitative approach using a case study. Researchers used interviews, observation, and documentation to collect the data. The research data were validated through the triangulation technique. Moreover, the data were analyzed using the data analysis techniques of the Miles, Huberman, and Saldana models, including data condensation, data presentation, and conclusion drawing. This research shows some activities to realize community-based education (CBE) in Madrasah Aliyah Nurul Mujtahidin Mlarak Ponorogo. They help the students find foster parents or sponsors and equip them with skills needed to plunge into community life, such as embroidery and sewing skills, screen printing, motorcycle workshops, computer services, blacksmith and steel processing.